A theoretical and experimental appraisal of five risk elicitation methods - Paolo Crosetto; Antonio Filippin (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
We perform a comparative analysis of five incentivized tasks used to elicit risk preferences. Theoretically, we compare the elicitation methods in terms of completeness of the range of the estimates as well as their precision, the likelihood of triggering loss aversion, and problems arising when multiple choices are required. Using original data from a homogeneous population, we experimentally investigate the distribution of estimated risk preferences, whether they differ by gender, and the complexity of the tasks. We do so using both non-parametric tests and a structural model estimated with maximum likelihood. We find that the estimated risk aversion parameters vary greatly across tasks and that gender differences appear only when the task is more likely to trigger loss aversion.
Keywords: C81; C91; D81; 330; Risk attitudes; Elicitation methods; Experiment